2013
DOI: 10.1021/ol4001087
|View full text |Cite
|
Sign up to set email alerts
|

Entry to β-Alkoxyacrylates via Gold-Catalyzed Intermolecular Coupling of Alkynoates and Allylic Ethers

Abstract: The first gold-catalyzed intermolecular coupling of alkynoates and allylic ethers invoking alkoxy addition and [3,3]-sigmatropic rearrangement as the key mechanism has been developed. Remarkably, the reaction showed complete chemoselectivity toward the pathway initiated by the alkoxy addition to alkynes. This unprecedented reactivity led to a new access to diversely substituted β-alkoxyacrylates in a highly efficient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…55 The observed regiochemistry as well as trapping experiments were consistent with a reaction proceeding through a highly distorted cyclopropyl gold( i ) carbene 15 , intermediate between 14a–c , which undergoes ring expansion to form cyclobutyl carbocation 16 . Related distorted cyclopropyl gold( i ) carbenes 15 (Scheme 7) were also proposed in the reaction of propiolic acid with alkenes 56 as well as in the addition of nucleophiles to enynes. 46,47,57,58 …”
Section: Gold Intermediatesmentioning
confidence: 99%
“…55 The observed regiochemistry as well as trapping experiments were consistent with a reaction proceeding through a highly distorted cyclopropyl gold( i ) carbene 15 , intermediate between 14a–c , which undergoes ring expansion to form cyclobutyl carbocation 16 . Related distorted cyclopropyl gold( i ) carbenes 15 (Scheme 7) were also proposed in the reaction of propiolic acid with alkenes 56 as well as in the addition of nucleophiles to enynes. 46,47,57,58 …”
Section: Gold Intermediatesmentioning
confidence: 99%
“…c Characterization data have been previously provided ([9]). d 15% of 4 (R 1 = Me) was observed for the reaction of 3i .…”
Section: Resultsmentioning
confidence: 99%
“…These indicated that a steric crowding in the proposed [3,3]-sigmatropic rearrangement transition state (Path A in Scheme 1) resulted in a sluggish reaction, but affected the competitive [1,3]-rearrangement less severely. It is noteworthy that an unsubstituted (R 2 , R 3 = H) allyl ether 2g afforded 3g in a good yield (Table 2, entry 7), unlike the reactions with propiolates [9] where only ~21% of carboalkoxylation product was obtained. However, a competition experiment using 3h having two different allyl groups showed that the more electron-rich allyl unit migrated exclusively (Table 2, entry 8), clearly indicating that an electron-rich R 2 substituent accelerated the [3,3]-sigmatropic rearrangement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations